1999
DOI: 10.1016/s0893-133x(99)00062-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of the Dopamine D1 Receptor in Human Caudate and Putamen

Abstract: Perturbations in the developmental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…Although all of the neurochemical "machinery" for dopaminergic transmission is present soon after birth, a number of indices of dopamine function change markedly during adolescence. Overexpression of dopamine D 1 , D 2 and D 4 receptors and subsequent decreases during adolescence have been reported in several studies [3,47,[65][66][67]. Such pruning has also been shown in postmortem studies of adolescent human brain for receptors and the dopamine transporter [44,57].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although all of the neurochemical "machinery" for dopaminergic transmission is present soon after birth, a number of indices of dopamine function change markedly during adolescence. Overexpression of dopamine D 1 , D 2 and D 4 receptors and subsequent decreases during adolescence have been reported in several studies [3,47,[65][66][67]. Such pruning has also been shown in postmortem studies of adolescent human brain for receptors and the dopamine transporter [44,57].…”
Section: Introductionmentioning
confidence: 71%
“…In fact, basal extracellular dopamine concentrations measured by microdialysis are reported to be lower than adult values in 33-43 day old rats [2] and in 35-36 day olds [36]. In contrast to lower extracellular dopamine in adolescents, striatal D 1 and D 2 receptor levels are higher in adolescent than adult humans [47,48,58] and rats [65,66]. The combination of more dopamine being released due to DAT inhibition onto more, or more sensitive, receptors could synergistically contribute to the greater behavioral response to cocaine that we reported [11].…”
Section: Discussionmentioning
confidence: 95%
“…In young rats, the relative populations of D1R and D2R and the proportion of each receptor at its high affinity state are not clear. Studies using quantitative autoradiography in rodents and primates showed that there was an initial overproduction followed by a declination of the dopamine D1R and D2R during adolescence [Montague et al, 1999;Andersen et al, 2000], although little evidence indicates that these two ontogenic processes are in synchrony. The rCBV decreases to cocaine and MPH challenge suggests that, at young ages, extracellular DA binds more efficiently to D2R than D1R.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are not surprising as the presence or absence of sex hormones is only one factor that could affect behavioral responsiveness to stimulants across adolescence. Forebrain dopamine systems continue to mature and reorganize across adolescence (Haycock et al 2003;Montague et al 1999;Teicher et al 1995;reviewed in Spear 2000). For example, it has been shown that there is an overproduction and regressive pruning of striatal dopamine receptors during adolescence (Teicher et al 1995).…”
Section: : Discussionmentioning
confidence: 99%